2021
DOI: 10.1111/jdv.17768
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Filaggrin and Claudin‐1 in the ocular surface of patients with atopic dermatitis

Abstract: Background Atopic dermatitis (AD) is an itchy, chronic and inflammatory skin condition, with dysfunctional immune response and skin barrier defects. Reduction of filaggrin (FLG) and tight junctions (TJ) proteins, such as claudin-1 (CLDN-1), expression in cutaneous epithelial barrier is remarkable in AD pathogenesis. Ocular involvement occurs in approximately 40% of AD patients leading to changes in the structure of the conjunctiva.Objectives We aimed to evaluate the expression of FLG and CLDN-1 in the ocular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…27 A study revealed that patients with AD had lower tear film breakup time (TBUT) values and impaired conjunctival epithelial barrier integrity, significantly different from the control group. 28 Ocular surface barrier lesion increases the penetration of allergens, bacteria and other substances, which increases susceptibility of AD patients to conjunctivitis. Furthermore, bacterial colonization of eyelids and conjunctival sac in AD patients was significantly higher, especially for Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A study revealed that patients with AD had lower tear film breakup time (TBUT) values and impaired conjunctival epithelial barrier integrity, significantly different from the control group. 28 Ocular surface barrier lesion increases the penetration of allergens, bacteria and other substances, which increases susceptibility of AD patients to conjunctivitis. Furthermore, bacterial colonization of eyelids and conjunctival sac in AD patients was significantly higher, especially for Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Toll‐like receptor‐2 gene −16,934 A > T polymorphism, an important genetic predictor, was found to be involved in the occurrence of allergic conjunctivitis and AD with higher Total serum IgE 27 . A study revealed that patients with AD had lower tear film breakup time (TBUT) values and impaired conjunctival epithelial barrier integrity, significantly different from the control group 28 . Ocular surface barrier lesion increases the penetration of allergens, bacteria and other substances, which increases susceptibility of AD patients to conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with biologics such as Dupilumab often leads to ocular adverse effects including conjunctivitis. Many patients affected by atopic dermatitis, however, had ocular problems prior to commencing biological treatment, as evidenced by increased expression of filaggrin and claudin‐1 on the ocular surface of atopic dermatitis patients 22 …”
Section: Atopic Dermatitis/eczemamentioning
confidence: 99%
“…Many patients affected by atopic dermatitis, however, had ocular problems prior to commencing biological treatment, as evidenced by increased expression of filaggrin and claudin-1 on the ocular surface of atopic dermatitis patients. 22 Current research on atopic dermatitis is also focusing on the role of the cutaneous microbiome and a Swiss group has recently discovered an increased fungal diversity in severe atopic dermatitis. 23 Additionally, topical application of commensal bacteria, such as Vitreoscilla filiformis, appears to be beneficial for certain patients.…”
Section: Atopic De R M At It Is/ Ecz E M Amentioning
confidence: 99%
“…It is estimated that between 7 and 20% of children and 7 to 14% of adults are affected by this globally. 80% of individuals develop symptoms within the first five years of life, and 60% of them suffer a recurrence in maturity (4) .…”
Section: Introductionmentioning
confidence: 99%